Revisiting the Foreign Direct Investment – Economic Growth Nexus: thresholds of absorptive capacity - Varum, C. A. (2012)
This paper revisits the relationship between FDI and economic growth. While the relationship between FDI, growth and the role of the moderating variable ‘absorptive capacity’ has been intensely debated, the identification of the minimum thresholds of absorptive capacity for a positive effect from FDI to arise remains largely unexplored. For this reason, two threshold variables - host country’s human capital level and the share of R&D performed by business sector on total GDP - are used as proxies for host countries’ absorptive capacity. The study is based on a sample of 30 countries of OECD for the period 1997-2007. The results confirm the suspicion that FDI effect on economic growth should not be taken for granted, even in developed countries, requiring the gathering of some conditions within host economies. By using the empirical setting of OECD countries for the period 1997-2007, our results are strongly supportive of a moderating effect played by both human capital and business sector R&D expenditures upon the growth enhancing effects of FDI. We contribute to the existing empirical evidence by quantifying the minimum thresholds required for countries to gain with FDI. It was found that the benefits from inward FDI in terms of growth only emerge when the country level of population with a college degree reaches about 27% and the share of business sector R&D in total GDP is about 1,4%. In 2007 a great portion of OECD countries still remain below both thresholds.